2017
DOI: 10.1101/cshperspect.a031435
|View full text |Cite
|
Sign up to set email alerts
|

KRAS: The Critical Driver and Therapeutic Target for Pancreatic Cancer

Abstract: RAS genes (HRAS, KRAS, and NRAS) comprise the most frequently mutated oncogene family in human cancer. With the highest RAS mutation frequencies seen with the top three causes of cancer deaths in the United States (lung, colorectal, and pancreatic cancer), the development of anti-RAS therapies is a major priority for cancer research. Despite more than three decades of intense effort, no effective RAS inhibitors have yet to reach the cancer patient. With bitter lessons learned from past failures and with new id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
580
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(594 citation statements)
references
References 106 publications
(146 reference statements)
10
580
2
2
Order By: Relevance
“…The KRAS oncogene encodes for a small GTPase which acts as a molecular switch bridging signals from membrane bound receptors to central cellular signaling pathways. The activity of KRAS is regulated by GTPase activating proteins (GAPs) and guanine exchange factors (GEFs) which toggle the protein between inactive (GDP bound) and active (GTP bound) states [9]. In PDA, KRAS is most commonly mutated at the G12 residue preventing the interaction with GAPs which results in KRAS bound to GTP and is therefore constitutively active [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KRAS oncogene encodes for a small GTPase which acts as a molecular switch bridging signals from membrane bound receptors to central cellular signaling pathways. The activity of KRAS is regulated by GTPase activating proteins (GAPs) and guanine exchange factors (GEFs) which toggle the protein between inactive (GDP bound) and active (GTP bound) states [9]. In PDA, KRAS is most commonly mutated at the G12 residue preventing the interaction with GAPs which results in KRAS bound to GTP and is therefore constitutively active [10].…”
Section: Introductionmentioning
confidence: 99%
“…These signaling pathways are responsible for regulating a number of key cellular functions including growth and survival. Unchecked KRAS signaling results in increased proliferation, decreased apoptosis, and an invasive phenotype [9]. While tumors require KRAS for growth, thus making it an attractive drug target, disrupting this oncogene pharmaceutically has proven problematic [11].…”
Section: Introductionmentioning
confidence: 99%
“…This ubiquitous oncogenic mutation is not only the initiating step of the pancreatic cancer progress but also associated with the driving force of tumor growth . Considerable studies have found that KRAS mutation is related to the aggressive pancreatic cancers and the short survivals of patients, suggesting that these genetic alterations would be the potential targets for antipancreatic cancer therapies . However, the clinical anti‐KRAS mutation therapies were compromised because of the undruggable properties of oncogenic KRAS .…”
Section: Introductionmentioning
confidence: 99%
“…[22] Considerable studies have found that KRAS mutation is related to the aggressive pancreatic cancers and the short survivals of patients, suggesting that these genetic alterations would be the potential targets for antipancreatic cancer therapies. [22,23] However, the clinical anti-KRAS mutation therapies were compromised because of the undruggable properties of oncogenic KRAS. [24] Therefore, silencing mutant KRAS via siRNA drugs might provide a promising alternative to the treatments of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The KRAS oncogene is mutated in >90% of pancreatic ductal adenocarcinoma (PDAC) (1) and oncogenic KRAS is critical for PDAC initiation and maintenance (2,3), making KRAS and its key effectors appealing targets for therapy. The oncogenic transcription factor MYC is well established as a critical effector of oncogenic RAS in multiple tumor types (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%